The effectiveness of advertising campaign on backache and backbone problems / Fatimah Nor Zahra Zakaria - Zakaria, Fatimah Nor Zahra (2013)
The study is to investigate and to find out about the problem of the backbone and backache. This study aims to give awareness to the society about the backache and to make them alert of the effects of this problem. In order to give awareness to the community about backache, there should be a method of telling people and the researcher will use advertising to solve the problem. The advertising about backache is lacking in our country and it is hard to persuade people to take a good care of their backbone and to give further information regarding the matter.